Metastasis of Malignant Melanoma in the Penile Urethra: A Rare Entity! - Magno Serrano, Pedro (2024)
Melanoma of the urogenital tract is extremely rare, accounting for less than 0.1% of melanoma cases. Currently, the literature describes only 220 cases of penile melanoma, most commonly located in the glans. The main challenge in penile melanoma, in addition to determining the cutaneous or mucosal origin, is early detection. The disease appears as a painless, pigmented lesion that gradually grows and then ulcerates. We describe the case of a 76-year-old patient who came to the emergency department due to left scrotal phlegmon with a suspicious penile lesion associated with mobile left inguinal adenopathy confirmed by ultrasound in another hospital unit. After diagnostic confirmation by excisional biopsy, staging was performed, showing multiorgan metastatic disease. Urology, Dermatology and Oncology are the specialties that should approach this type of cases in a multidisciplinary way, offering to the patient the best therapeutic option, since there are limitations in the literature regarding genitourinary mucosal melanoma. Treatment is surgical, including on the one hand conservative procedures for localized disease and on the other radical surgeries for locally advanced cases. Advanced disease may involve cytoreductive surgery as a bridge to palliative care and systemic chemotherapy.